EVALUASI POLA HIDUP ATLET RENANG PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGAPELAJAR(PPLP) JAWA TENGAH TAHUN 2016 - s, dimas s (Universitas Negeri Semarang, 2017)
The background of this research is patten life swimming athletes pplp central java. Based on the background the, the troubles in this research is nutritional intake, food consumption pattern, break the pattern, and activity outside schedule exercise swimming athletes pplp central java 2016.Methods used in this study uses the observation to technique interview. Population use swimming athletes pplp central java 2016 is estimated to 10 athletes and samples from 10 athletes taken a total of sampling. Data collection taken out schedule exercise.Analysis data using triagulasi.The results of the analysis data using triagulasi analysis, namely: 1). a method by using observation, interview, and table, 2). the source or information the coach and athletes swimming pplp central java, and 3). research in this study, researchers as observer directly in the field and as interviewer.Based on the results of above data can be concluded that the number of calories the average is weak are 9 athletes (90 %) have calory intake on the criteria less than 3000 calories and 1 athletes having calory intake on the criteria either above 3000 calories